Beef cattle value chain analysis: Evidence from West Hararghe Zone of Ethiopia - Adunea Dinku; Bezahagn Abebe; Azeb Lemma; Muhammed Shako (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
The study was initiated to identify beef cattle value chain actors and their roles, and investigate the determinants of quantity of beef cattle marketed. To achieve this, primary data were collected from randomly selected 171 cattle fatteners, 14 butcheries, 8 hotel and restaurant owners, 8 traders, and 6 consumers using pre-tested semi-structured questionnaire.